2018
DOI: 10.1111/bpa.12596
|View full text |Cite|
|
Sign up to set email alerts
|

New clinicopathological associations and histoprognostic markers in ILAE types of hippocampal sclerosis

Abstract: Mesial temporal lobe epilepsy with hippocampal sclerosis (MTLE-HS) is a heterogeneous syndrome. Surgery results in seizure freedom for most pharmacoresistant patients, but the epileptic and cognitive prognosis remains variable. The 2013 International League Against Epilepsy (ILAE) histopathological classification of hippocampal sclerosis (HS) has fostered research to understand MTLE-HS heterogeneity. We investigated the associations between histopathological features (ILAE types, hypertrophic CA4 neurons, gran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 50 publications
3
18
0
Order By: Relevance
“…In addition to spontaneous seizures, mTLE is characterized by profound hippocampal changes which include increased gliosis and decreased neuronal number [ 3 , 34 ]. Therefore, we assessed if reducing KCC2 activity in the hippocampus has any effects on these parameters.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to spontaneous seizures, mTLE is characterized by profound hippocampal changes which include increased gliosis and decreased neuronal number [ 3 , 34 ]. Therefore, we assessed if reducing KCC2 activity in the hippocampus has any effects on these parameters.…”
Section: Resultsmentioning
confidence: 99%
“…Granule cell dispersion is commonly associated with HS in TLE, noted in 76% of surgical specimens in a recent series 17 . In the context of HS, seizure-induced loss of reelinsynthesising interneurons has been shown to initiate neo-migration of mature granule cells 18 .…”
Section: Diminished Granule Cell Migration In Sudepmentioning
confidence: 89%
“…The dentate gyrus was also evaluated using a semiquantitative examination: 0 = normal granular cell layer, 1 = generalized or focal dispersion of granular cell layer, 2 = generalized or severe granular cell loss. When samples presented both dispersion and duplication, they were classified in the duplication subgroup . Two blinded observers performed the HS classification using a multi‐head microscope.…”
Section: Methodsmentioning
confidence: 99%
“…Patients with HS type 1 present earlier seizure onset than patients with HS types 2 or 3, but HS type 1 is related with better postoperative outcome . Recently, studies have shown association between neuronal loss and/or gliosis in the hippocampus with cognitive deficits, electrophysiological and magnetic resonance imaging (MRI) findings and psychiatric comorbidities in patients with TLE …”
Section: Introductionmentioning
confidence: 99%